Nueva especie de Loasa (Loasaceae) de Chile - MUÑOZ-SCHICK, MÉLICA; TRENQUALYE, ALAINDE (Gayana Botánica, 2011)
Loasa mollensis Muñoz-Schick et Trenqualye is described as a new species. It is apparently narrowly endemic to a small area in the coast of the Valparaiso region, central Chile. The species has small yellow flowers and infer rounded capsules containing large seeds.